Donovanosis (granuloma inguinale) of the oral cavity. Issue 2 (April 1975) - Garg, B R; Lal, S; Bedi, B M; Ratnam, D V; Naik, D N
Abstract : A female patient suffering from donovanosis of the oral cavity without associated lesions elsewhere is reported. The importance of remembering donovanosis in the differential diagnosis of chronic granulomatous ulceration of the mouth is emphasized.